2017
DOI: 10.1111/labr.12093
|View full text |Cite
|
Sign up to set email alerts
|

Wage Discrimination Against Immigrants in Austria?

Abstract: This paper analyses wage discrimination against immigrants in Austria using combined information from the labour force surveys and administrative social security data. We find that immigrants experience a wage penalty of 15 percentage points compared with natives. However, a substantial part of this gap can be explained by differences in human capital endowment and job position. Decomposition methods using quantile regressions indicate larger discrimination in the upper part of the wage distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 30 publications
1
18
0
2
Order By: Relevance
“…By the same token, physiological differences may have influenced the widely shared narratives of the three minority racial groups reported in this study. The latter also contributes to the emerging literature in Austria (Gärtner 2017;Hipfl and Gronold 2011;Hofer et al 2014;Huddleston and Tjaden 2012;Krzyzanowski 2017;Pechar 2015;Reichel and Perchinig 2015;Reichel 2012;Supik 2014;Rheindorf and Ruth 2019) on the intergenerational citizenry tensions between the 'Self' (indigenous-Austrians) and the 'Other' (Austrians from immigrant backgrounds). Even if locating the source of compressed social rights and entitlements exclusively within the construct of 'race' may be simplistic (Shutes 2016), the current endeavour suggests that 'race' or 'immigrant background' (popularly used in continental European literature) is a very important factor that exposes a colour-graded hierarchy of citizenship entitlements in Austria.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…By the same token, physiological differences may have influenced the widely shared narratives of the three minority racial groups reported in this study. The latter also contributes to the emerging literature in Austria (Gärtner 2017;Hipfl and Gronold 2011;Hofer et al 2014;Huddleston and Tjaden 2012;Krzyzanowski 2017;Pechar 2015;Reichel and Perchinig 2015;Reichel 2012;Supik 2014;Rheindorf and Ruth 2019) on the intergenerational citizenry tensions between the 'Self' (indigenous-Austrians) and the 'Other' (Austrians from immigrant backgrounds). Even if locating the source of compressed social rights and entitlements exclusively within the construct of 'race' may be simplistic (Shutes 2016), the current endeavour suggests that 'race' or 'immigrant background' (popularly used in continental European literature) is a very important factor that exposes a colour-graded hierarchy of citizenship entitlements in Austria.…”
Section: Discussionmentioning
confidence: 76%
“…Consistent with this assumption, other scholars have examined how the welfare state and social integration policies impact negatively upon the socioeconomic position and assimilation-levels of immigrants within communities (Gang et al 2002). Similarly, numerous other scholars (Gärtner 2017;Hofer et al 2014;Huddleston and Tjaden 2012;Pechar 2015;Reichel and Perchinig 2015;Reichel 2012) explored migratory trends and suggested that the vilification of the migrant population in Austria has been propelled by the contemporary racist political rhetoric compressed the civic rights of immigrants. It becomes apparent that the above studies have used the terms 'foreigners' or 'immigrants', etc., to lump together a diverse range of racial minority groups.…”
Section: State Of the Art In Literature: Austriamentioning
confidence: 95%
“…In terms of ethnic hierarchies, results of the main studies show several different patterns depending on the country analyzed. While the discrimination in Austria is highest for Arabs, followed by Chinese, Indians, Pakistani, and Bangladeshi (Hofer et al 2013 ), the results for Australia show the minimum level of discrimination for Italian immigrants followed by Aborigine candidates, Middle Eastern candidates, and Chinese (Booth et al 2012 ), and Ireland Asian immigrants are less discriminated than Germans and Africans (McGinnity and Lunn 2011 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Hofer et al . () merged information from the microcensus and administrative social security data to re‐examine the wage gap and found that immigrants earned 15% less than natives. About 10–30% of this wage gap can be explained by differences in human capital endowments.…”
Section: Introductionmentioning
confidence: 99%